An assessment of the impact of the black village communities, their associated land-use and related practices on water quality of the Kat River in the Eastern Cape, South Africa - Soviti, Malixole Knottien (Rhodes University, Faculty of Science, Department of Geography, 2002)
Amongst others, the South African National Water Act No. 36 of 1998 acknowledges that access to sufficient safe and clean water is a basic right to all South Africans. However, it is well known that millions of inhabitants of rural communities in South Africa are still deprived of this right. Many rural communities in South Africa are thus consuming unsafe, untreated water everyday, thereby exposing themselves to waterborne diseases. The main reason of concern however is the fact that, nevertheless, little is known about rural water quality in South Africa as most water quality work is being undertaken in urban areas. The study's aim is twofold: first, the study examines the impact of Black rural communities' land-use and related activities on water quality and second is specifically, to study the washing practices of the rural communities in the upper Kat River area. To understand the potential impacts of the upper Kat River Black village communities and their associated land-use practices on the quality of upper Kat River catchment, prominent land-use and related activities in the area were investigated. Study area maps were studied and field surveys undertaken to observe major land-use and related activities in the area. The results of the study show that most used land in the area is being utilised for agricultural activities. Settlements and commercial forestry also occupy considerable areas of land. The literature survey suggests that such land-use could have a considerable degrading impact on the quality of both surface and groundwater. The study also investigated the impact of the in-stream use of detergents on water quality in the upper Kat River valley, Eastern Cape - South Africa. In-stream washing practices of certain communities in the upper Kat River valley were investigated and the impact of detergents on water quality was assessed. Recovery of the flow from the input of detergents was also measured. During the study, it has been ascertained that doing laundry by the stream is the common practice in the study area. Water quality analysis results show a remarkable increase on the levels of chloride, turbidity, and electrical conductivity in water as a consequence of direct input of detergents practice into the river during the washing. The recovery of the water quality at a distance of 1km from site of input was almost complete. Water quality monitoring programme was undertaken to establish a link between land-use and the quality of water. In a water quality study routine carried out for a period of 40 weeks on a twice monthly frequency, the state of the flows of the river was determined; water samples were collected at pre-determined points; and the in situ analysis of selected water quality variables (with the exception of the faecal coliforms whose analysis was carried out in the biotechnology laboratory) was carried out. Results of the study showed that the concentration of the studied water quality variables in the area varied widely with time. A clear distinction in concentration of variables such as electrical conductivity, turbidity, pH, total hardness, chloride, and nitrate was evident at the high compared to the low flow period of the study. The concentration of the studied water quality variables in the upper Kat River catchment area also seemed to vary over space. The concentration of variables such as electrical conductivity, pH, total hardness, chloride, nitrate, potassium, number of faecal coliform bacteria per 100ml was observed to be higher in most of the tributary streams than the main river. Turbidity however was orders of magnitude higher in the Kat River than the rest of the tributaries. Most importantly however, results of the study showed that there is a strong link between the quality of water and land-use and related activities in the area. The spatial results of the study showed a strong connection between some land-use and the concentrations of water quality variables. For example, areas of intense grazing were noted with high concentrations of nutrients like nitrate and a higher number of faecal coliform bacteria per 100 ml of water. It was established during the study that land-use and related activities in the upper Kat River valley are negatively impacting on the quality of water thereby rendering it less fit for use for domestic purposes. The continued use of the polluted water by the communities is thus accompanied by a danger of the outbreak of waterborne diseases like cholera. When the concerned communities met in a workshop to discuss the issue of quality of their water, they committed themselves to: "¢ shunning water polluting activities, "¢ at least boiling their drinking water before consuming it. The communities also requested a meeting with the Department of Water and Forestry officials to request a treated, piped supply of water.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Water quality -- South Africa -- Kat River; Water -- Pollution -- South Africa -- Eastern Cape